Route Dominance on Symmetric Type Transit-based Evacuation Network - Adhikari, Ishwarmani (Kanya Journal, 2023)
The selection of dominant routes for transit-based evacuation planning problems mainly depends upon the structure and nature of the available network. To achieve efficient evacuation planning, the problem is not only on the selection of a route and a shelter for each route on the available network topology but also on the route-to-vehicle assignment and vice versa, which is more complex and challenging in real practice. The evacuation network adds complexity to the solution and impacts the problem. In this paper, the transit-based evacuation network has been revised from different perspectives focusing on the symmetric type networks with their dominant evacuation planning routes to have the minimum evacuation cost.